Flow conditions in the vicinity of microstructured interfaces studied by holography and implications for the assembly of artificial actin networks - Weiße, Sebastian; Heydt, Matthias Rudolf; Maier, Timo; Schulz, Simon; Spatz, Joachim P.; Grunze, Michael; Haraszti, Tamás; Rosenhahn, Axel (Physical chemistry, chemical physics, 2011)
Microstructured fluidic devices have successfully been used for the assembly of free standing actin networks as mechanical model systems on the top of micropillars. The assembly occurs spontaneously at the pillar heads when preformed filaments are injected into the channel. In order to reveal the driving mechanism of this localization, we studied the properties of the flow profile by holographic tracking. Despite the strong optical disturbances originating from the pillar field, 2 μm particles were traced with digital in-line holographic microscopy (DIHM). Trajectories in the pillar free region and local alterations of the flow profile induced by the channel structure in the pillar decorated region can be distinguished. Velocity histograms at different z-positions reveal that the laminar flow profile across the channel shows a difference between the minimum in the z-component of the velocity field and the maximum of the overall velocity. This minimum drag in vertical direction is present at the top of the pillars and explains why biopolymer networks readily assemble in this region instead of forming a homogeneous three-dimensional network in between the pillars. On the basis of the observations we propose a new mechanism for actin network formation on top of the microstructures.